Proceedings of the 2006 Conference on Interaction Design and Children 2006
DOI: 10.1145/1139073.1139082
|View full text |Cite
|
Sign up to set email alerts
|

On the design of Camelot, an outdoor game for children

Abstract: This paper describes the design of Camelot, a mobile outdoor game for small groups of children aged 7-9. The game was designed with the aim to encourage social interaction between the players and to encourage physical activity. The paper extends the research literature on design methodology for children, by recording and reflecting upon the lessons learnt by applying a range of techniques for involving children in the design of interactive systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…Camelot [9] represents a first attempt to design a head up game. It was developed over a course of 4 months, and during development it was repeatedly evaluated with a group of 10 children between 7 to 10 year old (see Figure 1).…”
Section: Camelotmentioning
confidence: 99%
“…Camelot [9] represents a first attempt to design a head up game. It was developed over a course of 4 months, and during development it was repeatedly evaluated with a group of 10 children between 7 to 10 year old (see Figure 1).…”
Section: Camelotmentioning
confidence: 99%
“…As an input to the design of Camelot [17], observations and interviews regarding what makes outdoor play fun for children showed that children favor games that are rich in physical activity.…”
Section: Physical Activitymentioning
confidence: 99%
“…Below we will mention the evaluation techniques and methods we have encountered that have successfully been used for the interactive play context once a proper experiment design is chosen. [266] or design [219].…”
Section: Evaluation Techniques and Methodsmentioning
confidence: 99%
“…For instance, Save the safe is a game that is played with a belt with a few LEDs and a vibration motor, where one player has a virtual key that is automatically passed when another player comes close, the burglars need to open a safe with the key in order to win [234]. Several other HUGs with accompanying handheld devices are mentioned/created, where players tag, shoot, collect, or hide someone/something [14,97,140,266]. Others have made use of the LEDs and accelerometer of the Sony Move controller.…”
Section: Playground Propsmentioning
confidence: 99%
See 1 more Smart Citation